2018
DOI: 10.3390/sym10110559
|View full text |Cite
|
Sign up to set email alerts
|

Charged and Non-Charged Black Hole Solutions in Mimetic Gravitational Theory

Abstract: In this study, we derive, in the framework of mimetic theory, charged and non-charged black hole solutions for spherically symmetric as well as flat horizon spacetimes. The asymptotic behavior of those black holes behave as flat or (A)dS spacetimes and coincide with the solutions derived before in general relativity theory. Using the field equations of non-linear electrodynamics mimetic theory we derive new black hole solutions with monopole and quadrupole terms. The quadruple term of those black holes is rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 121 publications
0
28
0
Order By: Relevance
“…Besides, many authors have considered different aspects of mimetic gravity during the last years with exciting results. Some examples are black holes [44][45][46][47][48][49][50][51][52][53][54], black strings [55], and braneworld scenarios [56][57][58][59][60][61], among others. For a more exhaustive survey, see and references therein.…”
Section: Jhep10(2020)150mentioning
confidence: 99%
“…Besides, many authors have considered different aspects of mimetic gravity during the last years with exciting results. Some examples are black holes [44][45][46][47][48][49][50][51][52][53][54], black strings [55], and braneworld scenarios [56][57][58][59][60][61], among others. For a more exhaustive survey, see and references therein.…”
Section: Jhep10(2020)150mentioning
confidence: 99%
“…They also revealed that these two solutions match continuously on the event horizon [27]. The authors of [28,29] considered static and rotating solutions of mimetic gravity with flat or cylindrical horizon in the presence of cosmological constant. However, the obtained solution in [28,29] are indeed nothing but the well-known black brane/string solutions of Einstein gravity.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [28,29] considered static and rotating solutions of mimetic gravity with flat or cylindrical horizon in the presence of cosmological constant. However, the obtained solution in [28,29] are indeed nothing but the well-known black brane/string solutions of Einstein gravity. The reason is that they have simply assumed g tt = −g rr , and arrived at a special solution of the mimetic field equations.…”
Section: Introductionmentioning
confidence: 99%
“…Inserting the vielbein (17) into field Eqs. (13) and 14, we obtain the following non-vanishing components:…”
Section: Asymptotically Static Ads Black Holesmentioning
confidence: 99%
“…Another proposal is f (T ) gravity in which T represents torsion scalar. Also in this case, for f (T ) = T , the theory reduces to the so called Teleparallel Equivalent General Relativity (TEGR) which is constructed by the Weitzenböck geometry and it is endowed with a nonsymmetric connection, characterized by no curvature and non-vanishing torsion [12][13][14][15]. The TEGR torsion tensor plays the dynamical role of curvature and the vielbein plays the role of metric tensor, that is the gravitational potentials.…”
Section: Introductionmentioning
confidence: 99%